2013
DOI: 10.19030/iber.v12i6.7868
|View full text |Cite
|
Sign up to set email alerts
|

The Explanatory Power Of The Yield Curve In Predicting Recessions In South Africa

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Mohapi and Botha () examine the predictive ability of the South African term spread, and those of China, the USA and Germany for South Africa's recessions. Results based on a dynamic probit model and quarterly data from 1980:1 to 2012:2 show that the South African term spread accurately predicted all the South Africa's recessions since 1980; the 1996 and 2008 recessions were accurately predicted by the Chinese term spread.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Mohapi and Botha () examine the predictive ability of the South African term spread, and those of China, the USA and Germany for South Africa's recessions. Results based on a dynamic probit model and quarterly data from 1980:1 to 2012:2 show that the South African term spread accurately predicted all the South Africa's recessions since 1980; the 1996 and 2008 recessions were accurately predicted by the Chinese term spread.…”
Section: Literature Reviewmentioning
confidence: 99%
“…From the South African studies, it seems that the best forecasting horizon is shorter (two quarters) than that obtained by most studies especially in the USA and Europe where the yield curve gives its best results in a forecasting horizon of four to eight quarters. Also aside from Mohapi and Botha (), these studies focused on in‐sample forecasting.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Majority of the earlier studies concentrated on the US economy (See Estrella and Hardouvelis, 1991;Stock and Watson, 1989;Turnovsky, 1989) while others covered some major countries in Europe (Berk and Van Bergeijk, 2000;Estrella and Mishkin, 1997;Davis and Fagan, 1997). For instance, Estrella and Hardouvelis, (1991) showed that the yield curve could be employed to provide useful information on the probability of US economy to experience recession (Mohapi and Botha, 2013). Apart from the US, it has been shown that the yield curve could predict recession in other countries such as Germany, France, Italy and the United Kingdom (Estrella and Mishkin, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In the event of an unanticipated economic slowdown, for instance, financial institutions risk the loss of funds due to low investment flows. This further impacts the labour market negatively as such periods are characterized by employee lay-offs, low tax revenue to government and widened budget deficit (Mohapi and Botha, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Even international studies have been done concerning the yield curve as a leading indicator of real growth. Nel (1 6 , Moolman (2002, Khomo and Aziakpono (2007and Mohapi and Botha (2013 for South Africa that there is evidence to support the yield curve as a leading indicator. For Europe, both Bonser and Morley (1 7 and Moneta (2005 show this link.…”
Section: Introductionmentioning
confidence: 99%